2018
DOI: 10.3766/jaaa.16114
|View full text |Cite
|
Sign up to set email alerts
|

Using a Digital Language Processor to Quantify the Auditory Environment and the Effect of Hearing Aids for Adults with Hearing Loss

Abstract: Background Auditory environments can influence the communication function of individuals with hearing loss and the effects of hearing aids. Therefore, a tool that can objectively characterize a patient’s real-world auditory environments is needed. Purpose To use the Language Environment Analysis (LENA) system to quantify the auditory environments of adults with hearing loss, to examine if the use of hearing aids changes a user’s auditory environment, and to determine the association between LENA variables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…For example, the older participants in the present study reported "Speech listen-ing, media" in approximately 30% of the EMA surveys (►Table 2). This is fairly similar to the time spent in television watching reported by Klein et al 30 ($26% of the time), Wu and Bentler 5 ($28% of the time), and Mares and Woodard 31 (3.5-3.8 hours/day). Of interest is that in the present study on average the participants reported "quiet" in the Noisiness question in 58% of the surveys (►Table 2).…”
Section: Test-retest Comparisonssupporting
confidence: 87%
“…For example, the older participants in the present study reported "Speech listen-ing, media" in approximately 30% of the EMA surveys (►Table 2). This is fairly similar to the time spent in television watching reported by Klein et al 30 ($26% of the time), Wu and Bentler 5 ($28% of the time), and Mares and Woodard 31 (3.5-3.8 hours/day). Of interest is that in the present study on average the participants reported "quiet" in the Noisiness question in 58% of the surveys (►Table 2).…”
Section: Test-retest Comparisonssupporting
confidence: 87%
“…Therefore, an unaided condition was included in the study in addition to the four HA conditions. Portions of the audio recording results (Klein et al 2018;Wu et al 2018) have already been published and will not be reported in the current paper. Furthermore, because the larger study also aimed to examine the test-retest reliability of the EMA methodology, participants repeated one of the four HA conditions (randomly selected) before the end of the study.…”
Section: Methodsmentioning
confidence: 99%
“…More analyses on the EMA data to explore the relationship between HA features and listening situations are needed. Further, the audio recordings collected for the larger study could be used to characterize the listening environments (Klein et al 2018;Wu et al 2018), which might be useful in explaining the effect of HAs and features in the real world. Average audiograms for left and right ears of study participants.…”
Section: Future Data Analysismentioning
confidence: 99%
“…The results of this study showed that MM alone provided the best speech recognition ability in a noisy environment for both adults and children, but this result should not be interpreted as a basis to deactivate a hearing aid microphone in noisy environments. For hearing-impaired children, hearing aid microphones can increase the chances of incidental learning (Vermeulen et al, 2012;Klein et al, 2018). HA + MM may be considered as a part of a more comprehensive program, where both target speech and incidental learning are desired.…”
Section: Discussionmentioning
confidence: 99%